Wave-induced seabed momentary liquefaction in shallow water. (October 2021) - Hsu, Cheng-Jung; Tsai, Chia-Cheng; Chen, Yang-Yih
Abstract: To realize seabed behaviours under extreme waves in coastal regions, a wave-induced seabed response subjected to high-order cnoidal wave theory is studied via Biot's consolidation theory. An analytical model is proposed for a dynamic response comprising pore pressure and effective stresses in a permeable layer of the seafloor. The seabed pressure solutions yielded by cnoidal waves up to the third order are derived as an input loading under boundary conditions, and high-power Jacobian elliptic cosine functions involved in cnoidal wave theory are approximated in terms of a Fourier series to construct the seabed response via the superposition of harmonic solutions. For the present Fourier series approximation of Jacobian elliptic cosine functions, a convergence analysis is performed, and a verification of seabed pressure compared with experimental data shows good agreement. The characteristics of the present solution are investigated, and the discrepancies among the solutions for each order and a harmonic solution for linear waves are demonstrated on the profiles of effective stresses and excess pore pressure. Compared with the third-order solution, the harmonic solution provides a better prediction at the wave peak than the other solutions, but the prediction of excess pore pressure around the wave trough shows a remarkable overestimation for every solution except the second-order solution. The impact of seabed momentary liquefaction induced by shallow water waves is evaluated, and the influence of wave parameters, including wave height and wavelength, is determined. This study reveals the significance of the nonlinear effect on seabed response under high-order cnoidal waves and provides the underlying implication to liquefaction assessment. Highlights: A novel analytical solution of seabed responses under third-order cnoidal wave theory is proposed for the first time. The third-order cnoidal wave solution shrinks the amplitude of the seabed surface pressure at both the wave peak and trough than the first-order solution. Compared with the third-order cnoidal wave solution, the prediction of excess pore pressure around the wave trough shows a remarkable overestimation for every solution except the second-order solution. Our analysis highlights the importance of adopting a high-order cnoidal wave solution to provide a more accurate prediction, particularly for the assessment of seabed liquefaction in shallow water.